Efficacy of Intralesional Alcohol Injection as Preoperative Treatment of Upper Lip Arteriovenous Malformation - Kreshanti, Prasetyanugraheni; Sudjatmiko, Gentur; Anindhawati, Nur (Jurnal Plastik Rekonstruksi, 2012)
Management of vascular malformation remains a major challenge because treatment carries a substantial risk of morbidity and recurrence of the fundamental problem. Intra-lesional 96% alcohol injection as a combination with other treatment modalities has good-to-excellent results. Six-year old female with a 5-year history of arteriovenous malformation on her upper lip underwent intralesional alcohol injection under general anesthesia. Afterward we performed excision of the lesion. During the surgery we used Satinsky intestinal clamp to control the bleeding by compressing the artery. The follow up period was 9 months; there were no complications and no signs of relapse. Aesthetically, the result perceived as acceptable to the parents and other viewers. In cases of arteriovenous malformation involving the lip the technique of injecting alcohol 96% intralesional in conjuct with reducing blood loss by using Satinsky intestinal clamps had an acceptable result aesthetically.